Beer Filtration using Cellulose Fibres – a Review - Braun, Frank; Back, Werner; Krottenthaler, Martin (BrewingScience, 2009)
Presently, kieselguhr filtration of beer is the most commonly used technology worldwide. Due to the growing problems with this filter aid, mainly concerning worker health and kieselguhr disposal, many alternatives have been investigated. Especially small and medium-sized breweries need solutions that allow existing equipment to be retrofitted. In the last decades, occasional articles treating the filtration of beer using cellulose fibres have been published. The properties of filter aids consisting exclusively of cellulose have been investigated as well as the properties of mixtures of cellulose and other filter aids. A lot of knowledge has thus been acquired. As a result of a systematic analysis of the existing literature on the topic, the important properties of cellulose-based filter aids are presented. Pre-coat filtration of beer by cellulose is possible. The beer has to be well pre-clarified. An economic technology, which would have to include a multiple regeneration of the filter aid, could not yet be found. Possible starting points for future investigations are named.